2022
DOI: 10.1002/jcla.24308
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in HIV‐positive patients: A systematic review of case reports and case series

Abstract: Introduction Coronavirus disease 2019 (COVID‐19) and acquired immune deficiency syndrome (AIDS) are two viral diseases for which there are currently no definitive treatments. Nowadays, because of the health system's focus on the COVID‐19 epidemic, the control of human immunodeficiency virus (HIV) has received less attention. In this review, we will discuss the characteristics of COVID‐19 in HIV‐positive patients. Material and Methods Using the PRISMA guideline, the databases of Scopus, PubMed, and Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Fever (70.37%) and respiratory failure (68.51%) were the most common symptoms of COVID‐19 in our evaluation. Heidary et al 19 achieved the same results in their study. They reported that clinical symptoms of COVID‐19 included coughing (81.3%), fever (62.8%), and dyspnea (60%).…”
Section: Discussionsupporting
confidence: 67%
“…Fever (70.37%) and respiratory failure (68.51%) were the most common symptoms of COVID‐19 in our evaluation. Heidary et al 19 achieved the same results in their study. They reported that clinical symptoms of COVID‐19 included coughing (81.3%), fever (62.8%), and dyspnea (60%).…”
Section: Discussionsupporting
confidence: 67%
“…Although studies have shown that underlying conditions cause the severity of COVID‐19 disease, but how each of these factors contribute to reinfection should be examined by designing new studies determining these effects separately or in combination. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity (32.5%), kidney failure (30.7%), and hypertension (30.1%) were the most frequent underlying comorbidities observed among COVID‐19 relapse patients. Although studies have shown that underlying conditions cause the severity of COVID‐19 disease, but how each of these factors contribute to reinfection should be examined by designing new studies determining these effects separately or in combination 28,29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection is asymptomatic or mild, but in most cases, it resembles the common cold ( 10 , 11 ). In more severe cases, the infection may clinically manifest as interstitial pneumonia with fever, cough, dyspnea, and bilateral infiltrates on chest imaging ( 12 , 13 ). It also may progress to acute respiratory distress syndrome, multiple-organ failure, and even death, likely as a consequence of excessive activation of the immune system that leads to a cytokine storm ( 14 ).…”
Section: Introductionmentioning
confidence: 99%